Determinants of equity changes in partial acquisitions of Finnish multinationals in foreign markets - Oguji, Nnamdi; Owusu, Richard A.; Larimo, Jorma (Emerald Publishing Limited, 2019)
Purpose – When entering foreign markets, multinationals can acquire part of a foreign firm and can increase or decrease their equity stake over time. However, extant studies have mainly focused on equity stake acquired during initial market entry. The paper aims to discuss this issue. Design/methodology/approach – This study fills this gap by using the Uppsala model to analyze six cases of international acquisitions of Finnish multinationals in global markets. Findings – The authors found that firms change their equity stake in partially acquired foreign subsidiaries: when they have learned about the host country and businesses of the partially acquired firms, when they have gained target-specific experience, when they build trust and ensure relationship commitment and finally, when they jointly develop and exploit opportunities. Originality/value – This study is one of the first to apply the Uppsala model to empirically analyze international acquisitions, thus paving the way for behavioral and process-oriented approaches. The study contributes to knowledge of post-entry strategies of multinationals.
Keywords: Equity changes; Internationalization process; Partial acquisition; Post-market entry; Staged acquisition; fi=Kansainvälinen liiketoiminta|en=International Business|